Judge Blaine Pettitt Retirement Luncheon at Fresno Hilton Hotel Ballroom - Watkins, Howard::::::::: (1985)
Judge Hollis Best speaking at lectern, Judge Robert Mardikian, Judge Blaine Pettitt, Alice Pettitt and Judge Denver C. Peckinpah seated at head table